A Retrospective Case-Control Study on the Risk Factors of Postpartum Hemorrhage - Sumaira Khoso, Anbia Soomro, Saira Hashmi, Pushpa Malhi, Tahmina Mahar, Erum Bano (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To determine the risk factors for postpartum hemorrhage. Study design:A retrospective case-control study Place and duration: This study was conducted at Bolan Medical College and Hospital Quetta from January 2021 to January 2022. Methodology: A total of 115 patients with PPH were identified in the given data.A case was categorized based on blood loss of more than 1500 mL or needing the transfusion of blood due to excessive postpartum blood loss. According to the exclusion criteria, those women who were transfused blood due to anemia were not included in the present study. A total of 225 cases were randomly chosen as controls. Those women did not report having PPH. Results: According to the data collected in our study, a total of 4695 babies were delivered in the given duration of time. Out of those, 115 were identified as cases and 225 were considered as random controls. The frequency of PPH was 2.45%. The commonest etiology of PPH was atony of the uterus (60%) and complications related to the placenta (36%). The risk factors determined to cause PPH was a positive history of PPH, anticoagulant drugs, anemia, severe pre-eclampsia, fibromas in the uterus, multiple pregnancies, and the use of assisted reproduction technologies. Conclusion: Patients having a positive history of PPH are most likely to develop severe PPH. It is the most significant risk factor. The most significant risk factor to cause severe PPH was a positive history of PPH, anticoagulation drugs, severe pre-eclampsia, anemia, multiple pregnancies, and uterine fibromas Keywords: Case-control study, postpartum hemorrhage, Risk factors, High-risk, Obstetric interventions